Knockdown of mineralocorticoid or angiotensin II type 1 receptor gene expression in the paraventricular nucleus prevents angiotensin II hypertension in rats. (22nd July 2014) - Chen, Aidong; Huang, Bing S.; Wang, Hong‐Wei; Ahmad, Monir; Leenen, Frans H. H.
<x xml:space="preserve">Abstract</x> Key points Chronic subcutaneous infusion of Ang II causes a progressive increase in blood pressure (BP) associated with significant increases in angiotensin type 1 receptor (AT1R) and mineralocorticoid receptor (MR) expression in hypothalamic nuclei. Intra‐paraventricular nucleus (PVN) infusion of AAV‐ AT1aR‐siRNA or of AAV‐MR‐siRNA markedly knockdown AT1a‐R or MR expression in the PVN but not in the subfornical organ; or supraoptic nucleus, and prevent most of the increase in BP. These findings indicate that increased MR and AT1R activation in the PVN play a critical role in Ang II‐induced hypertension in rats on regular salt intake. Abstract Circulating Ang II activates an aldosterone‐mineralocorticoid receptor (MR) – angiotensin II (Ang II) – angiotensin type 1 receptor (AT1R) pathway in the hypothalamus. To obtain insights into the actual neuronal projections involved, adeno‐associated virus carrying small interfering RNA against either AT1aR (AAV‐AT1aR‐siRNA) or MR (AAV‐MR‐siRNA) were infused into the paraventricular nucleus (PVN) in Wistar rats. Intra‐PVN infusion of AAV‐AT1aR‐siRNA or AAV‐MR‐siRNA decreased AT1R or MR expression in the PVN but not in the subfornical organ (SFO) or supraoptic nucleus (SON). Subcutaneous infusion of Ang II at 500 ng kg−1 min−1 for 2 weeks increased mean arterial pressure by 60–70 mmHg, and increased AT1R and MR expression in the SFO, SON and PVN. Intra‐PVN AT1aR‐siRNA prevented the Ang II‐induced increase in AT1R but not MR expression in the PVN, and MR‐siRNA prevented MR but not AT1R expression in the PVN. The increases in AT1R and MR expression in both the SFO and the SON were not changed by the two AAV‐siRNAs. Specific knockdown of AT1R or MR in the PVN by AAV‐siRNA each prevented most of the Ang II‐induced hypertension. Prevention of the subcutaneous Ang II‐induced increase in MR but not the increase in AT1R by knockdown of MR and vice versa suggests an independent regulation of MR and AT1R expression in the PVN. Both AT1R and MR activation in the PVN play a critical role in Ang II‐induced hypertension in rats.